Initiating disease-modifying treatments in multiple sclerosis: Measuring the decision process using decisional conflict and decisional regret scales. Issue 1 (February 2019) - Wilkie, DD; Solari, A; Nicholas, R
Introduction: Initiating disease-modifying treatments (DMTs) in multiple sclerosis (MS) is a major decision for people with (pw)MS but little is known about how the decision is perceived by the individual. Objectives: The aim of the study was to determine if decisional conflict (DC) and decisional regret reflect different stages of the decision-making process when initiating DMTs. Methods: This was a cross-sectional study of three cohorts of pwMS ( n = 254), a 'MS conference attendees', 'on treatment' and an 'offered treatment' cohort. Questionnaires assessing DC, decisional regret and control preference were performed. Results: Forty-four per cent (113/254) of pwMS were dissatisfied with their treatment status and 53% (135/254) had DC. DC ( p = 0.013) and decisional regret ( p = 0.027) increase in treatment-naïve pwMS and also in those 'offered treatment' dissatisfied with their treatment status ( p < 0.0001), whilst those 'on treatment' have low Decisional Regret Scale (DRS) score ( p = 0.0005). DC and DRS were only correlated with treatment status in those on treatment and not in treatment-naïve patients. Forty-three per cent (58/135) pwMS satisfied with treatment had DC. DC ( n = 236, adjusted R 2 0.137, p = 0.000) and DRS ( n = 235, adjusted R 2 0.232, p = 0.000) were increased by dissatisfaction with treatment, lower potency treatment, being from the 'MS conference attendees' cohort and reliance on the doctor's decision, with DC additionally associated with being employed. Conclusions: DC and decisional regret vary in populations at different stages of initiating DMTs and are impacted by non-treatment issues.